(untitled) (Journal of Academic Research, 2026)
A new series of random copolyesters V–VII was synthesized via interfacial polycondensation of dihydroxybenzylidene cyclohexanone derivatives with isophthaloyl and/or terephthaloyl dichlorides. The structures were confirmed by IR spectroscopy and elemental analysis, showing characteristic ester carbonyl bands. All copolyesters were insoluble in common organic solvents, indicating high molecular weight and ordered structures. Electrical measurements classified V and VII as insulators and VI as a semiconductor. Thermal analysis (TGA and DSC) revealed that VI had the highest initial thermal stability (374 °C), V the highest final stability (490 °C), and VII the highest Tg (68 °C) and Tm (235 °C), with increasing crystallinity from 32% to 37%, confirming that enhanced molecular regularity improves both thermal stability and crystallinity